Impact of Cardiac Rehabilitation on Functional Aerobic Capacity in Coronary Artery Disease Patients - Sjughiarto, M.Afies; Arso, Irsad Andi; Hartopo, Anggoro Budi (Advances In Social Humanities Research, 2025)
Cardiac rehabilitation (CR) is a vital component of secondary prevention in patients with coronary artery disease (CAD), known to improve cardiorespiratory fitness (CRF), enhance quality of life, and reduce cardiovascular morbidity and mortality. This study aimed to examine the impact of physical activity status on functional aerobic capacity (FAC) and CRF classification, as well as to identify significant predictors of FAC among CAD patients. A cross-sectional study was conducted involving 104 CAD patients who underwent exercise stress testing. Participants were divided into three groups: (1) those who completed phase II CR within 30 days, (2) those who engaged in regular exercise without formal CR, and (3) physically inactive individuals. FAC was calculated as the ratio of achieved to predicted metabolic equivalents (METs) and used to classify CRF into four categories (A: <69%, B: 70–99%, C: 100–129%, D: ?130%). The Kruskal-Wallis test revealed a significant association between rehabilitation status and FAC scores (p=0.047). Patients who completed phase II CR had significantly higher FAC than physically inactive individuals (p=0.011). The inactive group showed the lowest FAC (mean 0.58), with most classified in the lowest CRF category. Quantile regression demonstrated that phase II CR positively influenced FAC at the 50th and 75th quantiles (p=0.048 and p=0.011, respectively), while residual ischemia had a negative effect (p=0.005 and p=0.025). In conclusion, phase II CR significantly improves FAC in CAD patients, particularly those with moderate to high baseline capacity. Tailored CR programs may be especially beneficial for patients with residual ischemia, supporting individualized approaches in clinical rehabilitation practice.